Micron-scale hypervelocity impact craters: dependence of crater ellipticity and rim morphology on impact trajectory, projectile size, velocity, and shape - Wozniakiewicz, Penny; Price, M. C.; Armes, S. P.; Burchell, M. J.; Cole, M. J.; Fielding, L. A.; Hillier, Jon; Lovett, J. R. (Meteoritics & planetary science, 2014)
The interstellar collector on NASA's Stardust mission captured many particles from sources other than the interstellar dust stream. Impact trajectory may provide a means of discriminating between these different sources, and thus identifying/eliminating candidate interstellar particles. The collector's aerogel preserved a clear record of particle impact trajectory from the inclination and direction of the resultant tracks. However, the collector also contained aluminum foils and, although impact crater studies to date suggest only the most inclined impacts (>45° from normal) produce crater morphologies that indicate trajectory (i.e., distinctly elliptical), these studies have been restricted to much larger (mm and above) scales than are relevant for Stardust (μm). It is unknown how oblique impact crater morphology varies as a function of length scale, and therefore how well Stardust craters preserve details of impactor trajectory. Here, we present data from a series of impact experiments, together with complementary hydrocode modeling, that examine how crater morphology changes with impact angles for different-sized projectiles. We find that, for our smallest spherical projectiles (2 μm diameter), the ellipticity and rim morphology provide evidence of their inclined trajectory from as little as 15° from normal incidence. This is most likely a result of strain rate hardening in the target metal. Further experiments and models find that variation in velocity and impactor shape complicate these trends, but that rim morphology remains useful in determining impact direction (where the angle of impact is >20° from normal) and may help identify candidate interstellar particle craters on the Stardust collector.